Recent perspectives on the role of nutraceuticals as cholesterol-lowering agents - Ward, Natalie; Sahebkar, A.; Banach, M.; Watts, G. (Lippincott Williams & Wilkins, 2017)
Purpose of review Reduction in circulating cholesterol is an important step in lowering cardiovascular risk. Although statins are the most frequently prescribed cholesterol-lowering medication, there remains a significant portion of patients who require alternative treatment options. Nutraceuticals are increasingly popular as cholesterol-lowering agents. Despite the lack of long-term trials evaluating their use on cardiovascular endpoints and mortality, several studies have demonstrated their potential cholesterol-lowering effects. The purpose of this review is to provide an update on the role of nutraceuticals as cholesterol-lowering agents. The present review will focus on individual nutraceutical compounds, which have shown modest cholesterol-lowering abilities, as well as combination nutraceuticals, which may offer potential additive and/or synergistic effects. Recent findings Berberine, red yeast rice, and plant sterols have moderate potential as cholesterol-lowering agents. Combination nutraceuticals, including the proprietary formulation, Armolipid Plus, appear to confer additional benefit on plasma lipid profiles, even when taken with statins and other agents. Summary Although robust, long-term clinical trials to examine the effects of nutraceuticals on clinical outcomes are still required, their cholesterol-lowering ability, together with their reported tolerance and safety, offer a pragmatic option for lowering plasma cholesterol levels.